The Role of Small Lowland Patches of Exotic Forests as Refuges of Rare Endemic Azorean Arthropods - Tsafack, Noelline (2021)
Islands have been disproportionately affected by the current biodiversity crisis. In island biotas, one of the most recurrent anthropic alterations is species introduction. Invasion of exotic species may represent a major threat for island biotas, because invasive species may change species composition and simplify community dynamics. We investigated diversity patterns of native and introduced species in native and exotic forests of Terceira Island (Azores, Portugal) by using diversity profiles based on Hill numbers. Use of diversity profiles allows for a complete characterization of the community diversity because they combine information on species richness, rarity, and dominance. We found that native forest remnants are crucial for the maintenance of endemic Azorean arthropod diversity. However, we also found that some lowland patches of exotic forests can sustain populations of rare endemic species. Our findings reinforce the importance of the few and small remnants of native forests, which are a pillar to the conservation of Azorean endemic arthropods. However, areas occupied by exotic forests, whether they are large and contiguous or small and isolated, close to native forests, or embedded in a matrix of agriculture activities, can also play a role in the conservation of native species, including endemics.